(untitled) (Itinera, 2025)
This essay tracks the sudden bloom of AI-generated plants across social media and argues that their plausibility precipitates a crisis of ecological realism. These “algorithmic botanicals” borrow photography’s rhetoric of evidence while severing any indexical bond to the living world, producing images that are photographic without being photographs. Situating this phenomenon within lineages of realism—from Renaissance naturalism and Dutch still life to taxidermy, staged wildlife, and the spectacle— the essay shows how generative imagery weaponizes botanical desire for attention, clicks, and sales. The result is a miseducation of the gaze: an aesthetic norm calibrated to impossible perfection that diminishes the ordinary wonder of actual plants. Read through capitalist realism, AI flora offer frictionless connection without ecological consequence, anesthetizing care. The essay concludes by calling for new visual literacies and curatorial protocols, and by reframing realism as attunement—an ethics of looking that restores discernment between the living and the lifeless.